Weed Control in Eggplant - William M. Stall (EDIS)
Revised! HS-191, a 3-page fact sheet by William M. Stall, describes effective weed management practices for eggplant in Florida and provides a table listing herbicides available to growers for chemical weed control. This publication updates the 2003 table to reflect current recommendations. Published by the UF Department of Horticultural Sciences, October 2006.